How Important Are Value-Based Selling And Courteous Selling Behavior In Improving Salesforce Performance? - Paulus Wardoyo; Endang Rusdianti; Sri Purwantini (Integrated Journal of Business and Economics (IJBE), 2023)
This study aims to examine and analyze the role of value-based selling and courteous selling behavior in resolving the research gap between customer orientation and sales force performance. The population of this research is the salesforce at BPR Group Saudara in Central Java Province and DI Yogyakarta. The sampling technique used is purposive sampling, there are only 108 questionnaires that meet the requirements. The analysis technique uses structural equations, the solution is using SmartPLS version 3.2.9. The results show that one hypothesis is rejected, while the remaining five are accepted. In addition, the variable value-based selling and courteous selling behavior were not able to complete the research gap. However, value-based selling can mediate the influence of customer orientation on courteous behavior.